Factors Affecting The Income of Orange Farmers in Junrejo, Batu City - Anna Ismawati (International Research & Development for Human Beings (IRDH), 2024)
This research aims to determine several factors that influence the income of orange farmers in Junrejo District, Batu City. The research method used is quantitative, with data collection methods in the form of observation, documentation and questionnaires. From the results of multiple regression data processing, it shows that the factors that have a positive and significant influence in this research are farmers' capital and labor (farm laborers), while the length of farming business does not significantly influence the increase in income of orange farmers in Junrejo District, Batu City. Thus, the length of business cannot guarantee an increase in the income of orange farmers in Junrejo District, Batu City, the dominant one is farmer capital.